2004
DOI: 10.1097/00000542-200407000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Postoperative Pain Using an Intraoperatively Placed Epidural Catheter after Major Lumbar Spinal Surgery

Abstract: Continuous epidural infusion of 0.1% ropivacaine results in lower pain scores and opioid consumption and higher patient satisfaction when compared with placebo. Application of ropivacaine using an epidural catheter seems to be a highly effective treatment for postoperative pain after major lumbar spinal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 11 publications
1
65
0
7
Order By: Relevance
“…EA had not been used, and mean opioid doses were low compared with those in trials using patient-controlled Iv analgesia that demonstrated an average consumption of 150 mg oral morphine equivalents within the first 24 hours. 17,18 Even though open reduction of the calcaneus-the procedure with the highest pain score in this study-was associated with a comparatively high opioid administration of 40 mg, another trial demonstrated that patients used on average 167 mg Iv morphine via patientcontrolled anesthesia (approximately 500 mg oral morphine equivalents) during the first 24 h. 19 EA and peripheral nerve blocks are known to reduce postoperative pain intensity. 20 For many procedures, especially those that are known to cause severe postoperative pain, guidelines from many countries recommend the use of rA for postoperative pain control.…”
Section: Discussionmentioning
confidence: 67%
“…EA had not been used, and mean opioid doses were low compared with those in trials using patient-controlled Iv analgesia that demonstrated an average consumption of 150 mg oral morphine equivalents within the first 24 hours. 17,18 Even though open reduction of the calcaneus-the procedure with the highest pain score in this study-was associated with a comparatively high opioid administration of 40 mg, another trial demonstrated that patients used on average 167 mg Iv morphine via patientcontrolled anesthesia (approximately 500 mg oral morphine equivalents) during the first 24 h. 19 EA and peripheral nerve blocks are known to reduce postoperative pain intensity. 20 For many procedures, especially those that are known to cause severe postoperative pain, guidelines from many countries recommend the use of rA for postoperative pain control.…”
Section: Discussionmentioning
confidence: 67%
“…This includes multilevel instrumentation which is often associated with severe pain and consumption of large amounts of opioids thereby hindering postoperative mobilization and rehabilitation [3,4]. Also, patients undergoing major spine surgery often suffer from pre-operative chronic pain, further challenging postoperative pain treatment [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Before closure, an epidural catheter for postoperative pain management is inserted [17]. Autogenous bone from local bone resection is placed as posterior fusion material.…”
Section: Surgical Proceduresmentioning
confidence: 99%